A survey of the prevalence of fatigue, its precursors and individual coping mechanisms among U.S. manufacturing workers. (November 2017) - Lu, Lin; Megahed, Fadel M.; Sesek, Richard F.; Cavuoto, Lora A.
Abstract: Advanced manufacturing has resulted in significant changes on the shop-floor, influencing work demands and the working environment. The corresponding safety-related effects, including fatigue, have not been captured on an industry-wide scale. This paper presents results of a survey of U.S. manufacturing workers for the: prevalence of fatigue, its root causes and significant factors, and adopted individual fatigue coping methods. The responses from 451 manufacturing employees were analyzed using descriptive data analysis, bivariate analysis and Market Basket Analysis. 57.9% of respondents indicated that they were somewhat fatigued during the past week. They reported the ankles/feet, lower back and eyes were frequently affected body parts and a lack of sleep, work stress and shift schedule were top selected root causes for fatigue. In order to respond to fatigue when it is present, respondents reported coping by drinking caffeinated drinks, stretching/doing exercises and talking with coworkers. Frequent combinations of fatigue causes and individual coping methods were identified. These results may inform the design of fatigue monitoring and mitigation strategies and future research related to fatigue development. Highlights: Over 50% of respondents reported feeling fatigued in the past week. The ankles/feet, the lower back and eyes were most commonly affected. Combinations of root causes and individual coping measures for fatigue were identified by Market Basket Analysis.